2021
DOI: 10.32996/ijels.2021.3.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing ESL Primary School Teacher’s Readiness in Implementing CEFR-aligned Curriculum

Abstract: English as a Second Language (ESL) teachers in Malaysia, as in many other countries, are anxious to exploit the potential of Common European Framework of Reference (CEFR) –aligned curriculum to enhance the teaching and learning process. Given the increasing pressure exerted by various stakeholders on language education, it is important to understand the underlying factors behind primary school teachers’ readiness regarding CEFR-aligned curriculum. Even though there are studies conducted in local contexts, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Teacher preparedness for primary school readiness and transitioning was a crucial aspect of ensuring a smooth and successful transition for students. Several factors contributed to teacher preparedness in this regard teacher training, collaboration with other stakeholders, and capacity building on emerging issues like technology and their ability to align their ECE practices to national frameworks and higherlevel curricula (Yasin, 2021;Mambwe, 2019 andMambwe et al, 2019). To the contrary, this study demonstrated a lack of coordination, digital incompetence, and limited capacity building especially play-based learning.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Teacher preparedness for primary school readiness and transitioning was a crucial aspect of ensuring a smooth and successful transition for students. Several factors contributed to teacher preparedness in this regard teacher training, collaboration with other stakeholders, and capacity building on emerging issues like technology and their ability to align their ECE practices to national frameworks and higherlevel curricula (Yasin, 2021;Mambwe, 2019 andMambwe et al, 2019). To the contrary, this study demonstrated a lack of coordination, digital incompetence, and limited capacity building especially play-based learning.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Numerous investigations have thoroughly investigated the implementation of the CEFRaligned curriculum in the Malaysian English language [20][21][22][23][24]. The majority of these studies reference the introduction of newly imposed international textbooks in implementing the curriculum.…”
Section: Perceptions Of Imported Textbooksmentioning
confidence: 99%
“…The majority of these studies reference the introduction of newly imposed international textbooks in implementing the curriculum. Despite assertions by Yasin and Yamat (2021) regarding public approval, several reports present contrasting perspectives [23]. Numerous studies express strong stakeholder disapproval, citing concerns such as textbook costs, cultural aspects, and teacher challenges [21,24,25].…”
Section: Perceptions Of Imported Textbooksmentioning
confidence: 99%